Endocannabinoid Signaling Contributes to Experience-Induced Increase of Synaptic Release Sites From Parvalbumin Interneurons in Mouse Visual Cortex - Huang, Shiyong; Kirkwood, Alfredo (Frontiers in Cellular Neuroscience, 2020)
During postnatal development of visual cortex between eye-opening to puberty, visual experience promotes gradually increase in the strength of inhibitory synaptic connections from parvalbumin-positive interneurons (PV-INs) onto layer 2/3 pyramidal cells. However, the detailed connectivity properties and molecular mechanisms underlying this developmental change are not well understood. Using dual-patch clamp in brain slices from G42 mice, we revealed that both connection probability and the number of synaptic release site contributed to the enhancement of synaptic strength. The increase of release site number was hindered by dark rearing from eye-opening and rescued by 3-days reexposure to normal visual environment. The effect of light re-exposure on restoring synaptic release site in dark reared mice was mimicked by the agonist of cannabinoid-1 (CB1) receptors and blocked by antagonist of these receptors, suggesting a role for endocannabinoid signaling in light induced maturation of inhibitory connectivity from PV-INs to pyramidal cells during postnatal development. Keywords: